About pore structure of sugar beet pulp - Ivashchenko, Natalia; Bulyandra, Alexey; Verbitckiy, Boris; Lutsyk, Yuriy; Bernic, M.; Ciobanu, E. (My University, 2014)
The paper gives specific to beet pulp pore volume, integral and differential curves of micropore radii distribution, the effective radius of the pores. The effect of these parameters on the drying process has been shown.
Keywords: кафедра фізики та професійної безпеки; буряковий жом; розподіл мікропор; сушіння; сушка; sugar beet pulp; micro-pores; pores distribution; drying